Copper alloy powder for laminate shaping and method for producing same, and copper alloy laminate shaped
By adding an appropriate amount of aluminum to the copper alloy powder and grading a specific particle size, combining layer-layer shape and tempering treatment, the shortcomings of existing copper alloy layer-layer shapes in terms of mechanical strength and conductivity are solved, and high-quality Copper alloy layer stacking body properties.
Patent Information
- Application Number
- CN202380038983.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-04-27
- Publication Date
- 2024-12-17
AI Technical Summary
The existing copper alloy laminated shapes are difficult to achieve high-quality performance when taking into account both mechanical strength and conductivity, especially in terms of engineering stress, endurance and wear.
The copper alloy powder containing aluminum elements of more than 1.3% and less than 12.5% is used to generate and classify it into a particle size of more than 10 μm or less than 45 μm by gas atomization method, and the molding is carried out in combination with a layer-layer molding device, and tempering is carried out to improve the mechanical strength. .
A copper alloy layered layered body with high density and excellent mechanical strength has been achieved, with a relative density of more than 99.0%, Vickers hardness of more than 150 Hv, engineering stress of more than 500 MPa, endurance of more than 180 MPa and wear amount of less than 0.01 g.
Smart Images

Figure CN119156263A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to copper alloy powder for laminated molding and a method for producing the same, and a copper alloy laminated molding and a method for producing the same. Background Art
[0002] In the above-mentioned technical field, generally, there is a mutually restrictive relationship between the strength (hardness) and electrical conductivity of copper alloy stacked shapes. In Patent Documents 1 and 2, a copper alloy powder for stacked shapes is disclosed, which contains aluminum in an amount of not less than 0.2 mass % and not more than 1.3 mass %, and also contains copper and unavoidable impurities.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-115220
[0006] Patent Document 2: Japanese Patent No. 6532396 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, the copper alloy powders described in the above-mentioned documents cannot produce high-quality copper alloy laminated bodies.
[0009] An object of the present invention is to provide a technology for solving the above-mentioned problems.
[0010] Means for solving problems
[0011] In order to achieve the above-mentioned object, the copper alloy powder for laminated molding according to the present invention is a copper alloy powder for laminated molding used for molding a laminated body by a laminated molding method.
[0012] The copper alloy powder for laminated molding contains more than 1.3 wt % and less than 12.5 wt % of aluminum element, and the remainder is composed of copper and inevitable impurities.
[0013] In order to achieve the above-mentioned object, the present invention relates to a method for producing a copper alloy powder for stacking molding, which is the above-mentioned method for producing a copper alloy powder for stacking molding, and comprises the following steps:
[0014] A step of generating a copper alloy powder by gas atomization, wherein the copper alloy powder is obtained by adding more than 1.3 wt % and less than 12.5 wt % of aluminum to copper; and
[0015] A step of classifying the produced copper alloy powder into a particle size of 10 μm or more and 45 μm or less.
[0016] In order to achieve the above-mentioned object, the copper alloy laminated body according to the present invention is a copper alloy laminated body obtained by using the above-mentioned copper alloy powder for laminated forming and performing laminated forming using a laminated forming apparatus.
[0017] The copper alloy laminated body contains more than 1.3 wt % and less than 12.5 wt % of aluminum, and the remainder is composed of copper and inevitable impurities.
[0018] In order to achieve the above-mentioned object, the copper alloy laminated body according to the present invention is a copper alloy laminated body obtained by using the above-mentioned copper alloy powder for laminated molding and performing laminated molding using a laminated molding apparatus.
[0019] The copper alloy laminated body contains 7.0 wt % or more and 12.5 wt % or less of aluminum, and the remainder is composed of copper and inevitable impurities.
[0020] The copper alloy laminated body has a relative density of more than 99.0%, a Vickers hardness of more than 150 Hv, an engineering stress of more than 500 MPa, a bearing strength of more than 180 MPa, and a wear loss of less than 0.01 g.
[0021] In order to achieve the above-mentioned object, the manufacturing method of the copper alloy stacked shape body according to the present invention comprises the following steps:
[0022] A manufacturing process, using the above-mentioned copper alloy powder for stacking molding, and using a stacking molding device to manufacture a copper alloy stacked body; and
[0023] In the tempering step, the copper alloy laminated body is kept at a temperature of 400° C. to 600° C. for 1 hour.
[0024] Effects of the Invention
[0025] According to the present invention, a high-quality copper alloy laminated body can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] [ Figure 1 ] is a graph showing the relationship between the aluminum content of the copper alloy powder for laminated molding in Patent Document 1 and the relative density, electrical conductivity and engineering stress of the copper alloy laminated body.
[0027] [ Figure 2 ] is a diagram showing an example of the structure of the stacking forming device used in this embodiment.
[0028] [ Figure 3 ] is an optical microscope photograph showing the cross-sectional structure of the copper alloy laminated body obtained by laminated forming in Example 3 and a BC diagram and KAM diagram taken using the SEM / EBSD method.
[0029] [ Figure 4 ] is a diagram illustrating the measurement of the engineering stress, elongation and proof strength of the copper alloy laminated bodies in Examples 1 to 8 and Comparative Examples 0 to 6.
[0030] [ Figure 5 ] is a graph showing the relationship between the aluminum content of the copper alloy powder for laminated molding obtained in Examples 1 to 8 and Comparative Examples 0 and 1 and the engineering stress and proof strength of the copper alloy laminated body.
[0031] [ Figure 6 ] is a graph showing the relationship between the aluminum content of the copper alloy powder for laminated molding obtained in Examples 1 to 8 and Comparative Examples 0 and 1 and the wear amount of the copper alloy laminated molding.
[0032] [ Figure 7 ] is a diagram showing the quenching phase diagram of Cu-Al alloy and the calculation of the forming threshold.
[0033] [ Figure 8 ] is a graph showing the relationship between the tempering temperature of the copper alloy laminated body obtained in Example 4 and the engineering stress and proof strength of the copper alloy laminated body.
[0034] [ Fig. 9 ] is a diagram showing the equilibrium phase diagram of Cu-Al alloy. DETAILED DESCRIPTION
[0035] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the components described in the following embodiments are merely illustrative, and the technical scope of the present invention is not limited thereto.
[0036] [First embodiment]
[0037] In this embodiment, a copper alloy powder for laminated molding that can obtain a copper alloy laminated body having sufficient mechanical strength (engineering stress, endurance, or wear resistance) is described. Prior to this, the current status of copper alloy powder for laminated molding is first described.
[0038] <Current Status of Copper Alloy Powder for Laminated Molding>
[0039] The stacking molding technology can produce products with complex shapes that are difficult to produce with conventional processing technologies, and its application in various fields is expected. In particular, the application of metal materials with excellent mechanical properties is expected. Among metal materials, copper has excellent electrical conductivity and thermal conductivity, and therefore, the application of stacking molding in products with complex shapes such as normal radiators and heat exchangers is expected.
[0040] However, as in Patent Documents 1 and 2, since copper alloy powder having both mechanical strength and electrical conductivity is required, sufficient results have not been obtained in terms of mechanical strength, i.e., engineering stress (maximum stress), endurance (endurance or 0.2% offset yield strength), or wear resistance (amount of wear), etc. of copper alloy laminated bodies containing aluminum elements. Therefore, the use of copper alloy laminated bodies is also limited.
[0041] For example, the properties of the copper alloy laminated bodies containing aluminum in Patent Documents 1 and 2 are as follows: Figure 1 That is, in Patent Documents 1 and 2, it is shown that by using a copper alloy powder containing 0.2 mass % or more and 1.3 mass % or less of aluminum element, a copper alloy laminated body having a relative density of 96% or more and 100% or less, an electrical conductivity of 30% IACS or more, and an engineering stress (maximum stress) of 130 MPa or more and 250 MPa or less is obtained.
[0042] <Copper Alloy Powder for Laminated Forming of the Present Embodiment>
[0043] In the present embodiment, a copper alloy powder for stacking molding is provided, which has a particle shape, particle size, apparent density and fluidity suitable for a stacking molding method based on a stacking molding device, and the copper alloy powder for stacking molding can be used for stacking molding of copper alloy stacked bodies with excellent mechanical strength, i.e., engineering stress, endurance, or wear resistance.
[0044] (Conditions of copper alloy powder for laminated molding)
[0045] The following conditions are required for the copper alloy powder that can be laminated and molded using a laminate molding apparatus.
[0046] (1) The 50% particle size of the copper alloy powder particles measured by the laser diffraction method is in the range of 3 μm to 200 μm. When the 50% particle size of the copper alloy powder particles is less than 3 μm, there is no fluidity, and a powder bed cannot be formed even in a stacking molding device of the SLM method. On the other hand, when the 50% particle size of the copper alloy powder particles is greater than 200 μm, the surface of the powder bed is rough and a powder bed suitable for molding cannot be formed even in a stacking molding device of the EBM method.
[0047] (2) The apparent density (AD) of the copper alloy powder is 3.0 g / cm 3 When the apparent density of the copper alloy powder is less than 3.0, the powder filling rate of the powder bed in the layered molding apparatus decreases, and an appropriate powder bed cannot be formed.
[0048] (3) The fluidity (FR: flow rate) of the copper alloy powder is less than 60 seconds / 50 g. When the fluidity of the copper alloy powder is more than 60 seconds / 50 g, the powder cannot be supplied from the supply hopper in the stacking forming device, and a proper powder bed cannot be formed. It should be noted that when the fluidity (FR) cannot be measured, the adhesion of the copper alloy powder (calculated from the failure envelope obtained by a shear test using a powder rheometer) is less than 0.600 kPa. When the adhesion of the copper alloy powder is more than 0.600 kPa, the powder cannot be supplied from the supply hopper in the stacking forming device, and a proper powder bed cannot be formed.
[0049] (Method for producing copper alloy powder for laminated molding)
[0050] The copper alloy powder for stacking molding of the present embodiment can be manufactured by, for example, a "rotating disk method", "gas atomization method", "water atomization method", "plasma atomization method", "plasma rotating electrode method", etc. In the present embodiment, the "gas atomization method" among them is used, and a gas such as helium, argon, and nitrogen is used as the spray gas, and the pressure and flow rate of the gas are adjusted to manufacture the copper alloy powder, but the same copper alloy powder can also be manufactured by other manufacturing methods. The manufactured copper alloy powder is classified into a predetermined particle size (for example, 10 μm or more and 45 μm or less).
[0051] (Determination of properties of copper alloy powder for laminated molding)
[0052] The following properties were measured for the produced copper alloy powder for laminated molding.
[0053] (1) The aluminum content of a copper alloy powder obtained by adding aluminum to copper was measured by ICP (Inductively Coupled Plasma) emission spectrometry.
[0054] (2) The apparent density (g / cm2) of the copper alloy powder to which aluminum was added was measured according to the JIS Z 2504 method. 3 ).
[0055] (3) The flowability (seconds / 50 g) of the copper alloy powder to which aluminum element was added was measured according to the measurement method of JIS Z 2502.
[0056] (4) The adhesion of the copper alloy powder was measured as an index of fluidity based on the fracture envelope obtained by a shear test using a powder rheometer.
[0057] (5) The 50% particle size (μm) was measured by laser diffraction.
[0058] (Evaluation of measurement results)
[0059] The copper alloy powder for lamination molding to which aluminum element is added in an amount of not less than 0.6 wt % and not more than 14.0 wt % in this embodiment satisfies the above-mentioned conditions for lamination molding using a lamination molding apparatus, although the fluidity measurement (3) cannot be performed. That is, the powder satisfies any of the following conditions: (1) 50% particle size of the copper alloy powder particles, (2) apparent density of the copper alloy powder, and (3) adhesion of the copper alloy powder (although the fluidity itself cannot be measured).
[0060] <Manufacturing of the Laminated Structure of the Present Embodiment>
[0061] Figure 2 : This is a diagram showing a schematic configuration example of a stacking forming device 200 of the present embodiment. The stacking forming device 200 has: an emitting mechanism 201 of an electron beam or a laser 201a; a feed hopper 202, which is a powder tank; a scraper 203, which is used to form a powder bed covered with powder at a certain thickness; and a platform 204, which is repeatedly lowered by a certain thickness for stacking. Through the cooperation of the scraper 203 and the platform 204, a uniform powder stacking portion 205 of a certain thickness is generated. For each layer, an electron beam or a laser 201a is irradiated based on the slice data obtained from the 3D-CAD data to melt the metal powder (copper alloy powder in this embodiment), thereby manufacturing a stacked forming body 205a.
[0062] It should be noted that the energy density ED (J / mm 3 ) is adjusted according to ED=LP / (SS×HP×LT). Here, LP: laser output power (W), SS: laser scanning speed (mm / s), HP: laser scanning distance (mm), LT: thickness of powder bed (mm) (see Table 2).
[0063] (Conditions for stacking shapes)
[0064] The following conditions are required as a useful laminated structure of the present embodiment. It should be noted that the following conditions are conditions for obtaining a desired mechanical strength of the copper alloy laminated structure.
[0065] (1) The laminated body using the copper alloy powder has a sufficient relative density, for example, a relative density of 99.0% or more.
[0066] (2) The Vickers hardness of the laminated structure is 90.0 Hv or more, preferably 150.0 Hv or more.
[0067] (3) The engineering stress of the laminated structure is 260.0 MPa or more, preferably 500.0 MPa or more.
[0068] (4) The proof strength of the laminated structure is 160.0 MPa or more, preferably 200.0 MPa or more.
[0069] (5) The wear amount of the laminated structure is 0.02 g or less, preferably 0.01 g or less.
[0070] (Determination of properties of laminated structures)
[0071] The following properties of the manufactured laminated structure were measured.
[0072] (1) Using an optical microscope and SEM (Scanning Electron Microscope) / EBSD (Electron Back Scatter Diffraction) method, the structure of the cross section of the manufactured stacked structure and the BC (Band Contrast) map and KAM (Kernel Average Misorientation) map were photographed.
[0073] (2) The layered structure and a powder having the same composition as the layered structure were measured by the Archimedean method, and the relative density (%) of the layered structure was calculated by setting the density of the powder to 100%.
[0074] (3) The Vickers hardness (Hv) of the laminated structure was measured using a micro hardness tester.
[0075] (4) The engineering stress (MPa: maximum stress), elongation (%) and proof strength (MPa) of the laminated body were measured using a universal material testing machine.
[0076] (5) The wear amount (g) of the laminated structure was measured using a multifunctional wear tester.
[0077] (6) The electrical conductivity (% I ACS) of the laminated structure was measured using an eddy current conductivity meter.
[0078] (Evaluation of measurement results)
[0079] By using the copper alloy powder for stacking molding containing more than 1.3 mass % and less than 12.5 mass % of aluminum element in this embodiment, a stacking body that satisfies the above conditions, i.e., (1) a relative density of 99.0% or more, is manufactured. In addition, a stacking body that satisfies (2) a Vickers hardness of 90.0 Hv or more is manufactured. In addition, a stacking body that satisfies (3) an engineering stress of 260.0 MPa or more and (4) a stacking body endurance of 160.0 MPa or more is manufactured. In addition, a stacking body that satisfies (5) a wear amount of the stacking body of 0.02 g or less is manufactured.
[0080] In addition, by using a copper alloy powder for stacking molding containing 7.0 mass % or more and 12.5 mass % or less of aluminum elements, a copper alloy stacking body can be obtained having a relative density of 99.0% or more, a Vickers hardness of 150.0 Hv or more, an engineering stress (maximum stress) of 500 MPa or more, a resistance of 180 MPa or more, and a wear amount of 0.01 g or less.
[0081] (Composition of Copper Alloy Powder Suitable for Laminated Forming)
[0082] In this embodiment, an appropriate amount of aluminum element is added to copper to provide a copper alloy powder that satisfies the conditions for being paintable for stacking molding, and the stacked body after stacking molding using a stacking molding device has a sufficient relative density and mechanical strength sufficient to be used as a mechanical product or component.
[0083] The copper alloy powder for laminated molding of the present embodiment preferably contains more than 1.3% by weight and less than 12.5% by weight of aluminum, with the remainder being copper and inevitable impurities. More preferably, it is a copper alloy powder for laminated molding containing 1.7% by weight or more and less than 12.5% by weight of aluminum. Still more preferably, it is a copper alloy powder for laminated molding containing 7.0% by weight or more and less than 12.5% by weight of aluminum.
[0084] <Effects of the present embodiment>
[0085] According to the present embodiment, a copper alloy powder for laminated molding to which an aluminum element is added in an amount of more than 1.3 wt % and 12.5 wt % or less can be provided, and a copper alloy laminated molding having a high density and excellent mechanical strength can be obtained.
[0086] That is, since the 50% particle size of the copper alloy powder particles measured by laser diffraction is within the range of 3 μm to 200 μm, the surface of the powder bed is not rough and has sufficient fluidity for easy application. In addition, since the apparent density of the copper alloy powder is 3.5 g / cm 3As a result, the powder filling rate of the powder bed is sufficient, and an appropriate powder bed can be formed. In addition, since the adhesion of the copper alloy powder is 0.600 kPa or less, the powder can be smoothly supplied from the supply hopper, and an appropriate powder bed can be formed.
[0087] Furthermore, by adding an aluminum element in an amount of greater than 1.3 wt % and less than 12.5 wt %, a copper alloy laminated body can be manufactured whose relative density of the body when molded under conditions set based on energy density (which can be calculated from the output power of the laser, the scanning speed of the laser, the laser scanning interval, and the thickness of the powder bed) is greater than 99.0%. In addition, a copper alloy laminated body with a Vickers hardness of greater than 90 Hv, an engineering stress of greater than 260 MPa, a resistance of greater than 160 MPa, and a wear loss of less than 0.02 g can be manufactured.
[0088] In addition, by adding aluminum elements in an amount greater than 7.0 wt. % and less than 12.5 wt. %, a copper alloy stacked shape can be manufactured with a relative density of greater than 99.0%, a Vickers hardness of greater than 150 Hv, an engineering stress of greater than 500 MPa, a resistance of greater than 180 MPa, and a wear amount of less than 0.01 g.
[0089] [Second embodiment]
[0090] In this embodiment, the copper alloy laminated body obtained by laminated molding using the copper alloy powder for laminated molding of the first embodiment is further subjected to tempering treatment, thereby improving mechanical strength, especially endurance. It should be noted that the production of the copper alloy powder for laminated molding before tempering treatment and the production of the copper alloy laminated body using the copper alloy powder for laminated molding are the same as those in the first embodiment, so repeated descriptions are omitted. In addition, in this embodiment, the copper alloy powder for laminated molding containing 10.0% by weight of aluminum is used as an example for description, but the same effect can be achieved in the copper alloy laminated body obtained by laminated molding using other copper alloy powders for laminated molding containing aluminum elements.
[0091] <Tempering Treatment of the Laminated Shaped Body of the Present Embodiment>
[0092] The copper alloy stacked body obtained by stacking and molding the copper alloy powder for stacking molding according to the first embodiment (aluminum content is 10.0 weight%) was annealed in a hydrogen atmosphere by changing the temperature from 400°C to 600°C (above 400°C and below 600°C) and maintaining it for 1 hour (60 minutes).
[0093] (Effect of tempering treatment)
[0094] As the tempering temperature increases from 400°C to 600°C, the engineering stress decreases linearly from 894.98MPa to 591.90MPa, while the endurance strength increases from 188.70MPa to above 253.60MPa.
[0095] <Effects of the present embodiment>
[0096] According to the present embodiment, by subjecting the copper alloy multilayer structure to tempering, it is possible to obtain a copper alloy multilayer structure having improved resistance and being less likely to be deformed by external force.
[0097] [Third Embodiment]
[0098] In this embodiment, a copper alloy powder for laminated formation is prepared by further adding iron (Fe), nickel (Ni), and manganese (Mn) to the copper alloy powder for laminated formation of the first embodiment. A laminated object is formed using the copper alloy powder for laminated formation thus prepared.
[0099] The following effects can be obtained by adding iron, nickel and manganese.
[0100] (Addition of iron)
[0101] The solid solubility limit of the α phase caused by the addition of the iron element is such that it slightly affects the solid solubility limit of aluminum in copper.
[0102] · Regarding the eutectoid transformation rate (β→α+γ 2 ) delays the transition of the low temperature part.
[0103] · In the metal structure, κ phase (σ-Fe or Fe-Ni) is precipitated. The κ phase tends to become a coarse precipitated phase like a dendrite as the amount of Fe added increases. If about 3.5 wt% or more of Fe is contained, the κ phase as the primary crystal effectively refines the solidified structure of the β phase.
[0104] (Addition of Nickel)
[0105] The addition of nickel increases the solid solubility limit of the α phase, expands the α phase region, and reduces the stability of the β phase, thereby promoting eutectoid transformation.
[0106] · Regarding the eutectoid transformation rate (β→α+γ 2 ), it slightly promotes the start of the eutectoid transformation, but on the other hand, has the effect of delaying the end of the transformation.
[0107] · In the metal structure, a κ phase (Ni—Al) is precipitated. The precipitation of the κ phase imparts aging hardenability to the aluminum bronze.
[0108] By the above-mentioned (addition of iron element) and (addition of nickel element), the solidification structure is refined, and a uniformly dispersed κ phase can be obtained, so that the "engineering stress (maximum stress)" and "endurance" are improved. In addition, the mechanical properties can be easily improved by heat treatment, and the "endurance" can be improved in particular.
[0109] (Addition of manganese)
[0110] The α phase solid solubility limit caused by the addition of manganese has no effect on the precipitation shapes of the α phase and the κ phase up to about 1 wt %. However, there is a tendency for the α phase region to shrink as the amount of manganese increases.
[0111] · Regarding the eutectoid transformation rate (β→α+γ 2 ), the eutectoid transformation is significantly delayed. In addition, the transition temperature is significantly reduced.
[0112] In the metal structure, in the case of a high manganese composition, Cu3Mn2Al phase precipitates in the β phase and the α phase.
[0113] By adding the manganese element as described above, the eutectoid transformation of the β phase is delayed, so that even with slow cooling, the fragile γ phase can be prevented from 2 In addition, as the amount of Mn increases in order to reduce the α phase region, the “engineering stress (maximum stress)”, “proof strength” and “Vickers hardness” increase.
[0114] The method of adding the iron element, the nickel element, and the manganese element in this embodiment is the same as the method of adding the aluminum element in the first embodiment. In this embodiment, a copper alloy powder for laminated molding containing 7.0 wt% to 12.5 wt% of aluminum element, 1.0 wt% to 6.0 wt% of iron element, 0.1 wt% to 6.0 wt% of nickel element, and 0.1 wt% to 1.5 wt% of manganese element is manufactured.
[0115] Then, the following properties were measured for the produced copper alloy powder for laminated molding.
[0116] (1) The contents of aluminum, iron, nickel, and manganese in the produced copper alloy powder were measured by ICP (Inductively Coupled Plasma) emission spectrometry.
[0117] (2) The apparent density (g / cm2) of the produced copper alloy powder was measured according to the measurement method of JIS Z 2504. 3 ).
[0118] (3) The flowability (seconds / 50 g) of the produced copper alloy powder was measured according to the measurement method of JIS Z 2502.
[0119] (4) The adhesion of the produced copper alloy powder was measured as an index of fluidity based on the fracture envelope obtained by a shear test using a powder rheometer.
[0120] (5) The 50% particle size (μm) of the produced copper alloy powder was measured by laser diffraction method.
[0121] (Evaluation of measurement results)
[0122] Although the copper alloy powder for laminated molding in this embodiment cannot be measured for fluidity (3), it satisfies the above-mentioned conditions for laminated molding using a laminated molding apparatus. That is, it is a powder that satisfies any of the following conditions: (1) 50% particle size of copper alloy powder particles, (2) apparent density of copper alloy powder, and (3) adhesion of copper alloy powder (although fluidity itself cannot be measured).
[0123] That is, the following conditions are satisfied similarly to the copper alloy powder for laminated molding according to the first embodiment.
[0124] (1) The 50% particle size of the copper alloy powder particles measured by a laser diffraction method is in the range of 3 μm or more and 200 μm or less.
[0125] (2) The apparent density (AD) of the copper alloy powder is 3.0 g / cm 3 above.
[0126] (3) The flow rate (FR) of the copper alloy powder is 60 seconds / 50 g or less. When the flow rate (FR) cannot be measured, the adhesion of the copper alloy powder (obtained from the fracture envelope obtained by a shear test using a powder rheometer) is 0.600 kPa or less.
[0127] Next, the same as in the first embodiment is used. Figure 2 The laminated forming apparatus 200 shown in the figure forms a laminated formed object using the copper alloy powder for laminated forming produced. It should be noted that the energy density ED (J / mm 3 ) is adjusted according to ED=LP / (SS×HP×LT). Here, LP: laser output power (W), SS: laser scanning speed (mm / s), HP: laser scanning distance (mm), LT: thickness of powder bed (mm) (see Table 9).
[0128] The following properties were measured for the obtained laminated structure.
[0129] (1) The structure of the cross section of the manufactured laminated structure and the BC (Band Contrast) map and KAM (Kernel Average Misorientation) map were photographed using an optical microscope and the SEM (Scanning Electron Microscope) / EBSD (Electron Back Scatter Diffraction) method.
[0130] (2) The layered structure and a powder having the same composition as the layered structure were measured by the Archimedean method, and the relative density (%) of the layered structure was calculated by setting the density of the powder to 100%.
[0131] (3) The Vickers hardness (Hv) of the laminated structure was measured using a micro hardness tester.
[0132] (4) The engineering stress (MPa: maximum stress), elongation (%) and proof strength (MPa) of the laminated body were measured using a universal material testing machine.
[0133] (5) The wear amount (g) of the laminated structure was measured using a multifunctional wear tester.
[0134] (6) The electrical conductivity (% I ACS) of the laminated structure was measured using an eddy current conductivity meter.
[0135] (Evaluation of measurement results)
[0136] By using the copper alloy powder for stacking molding in this embodiment that contains 7.0 mass % to 12.5 mass % of aluminum, 1.0 weight % to 6.0 weight % of iron, 0.1 weight % to 6.0 weight % of nickel, and 0.1 weight % to 1.5 weight % of manganese, it is possible to obtain a copper alloy stacking body having a relative density of 99.0% or more, a Vickers hardness of 150.0 Hv or more, an engineering stress (maximum stress) of 500 MPa or more, a resistance of 180 MPa or more, and a wear amount of 0.01 g or less.
[0137] <Effects of the present embodiment>
[0138] According to this embodiment, a copper alloy powder for stacking molding can be provided to which is added 7.0 mass % to 12.5 mass % of aluminum element, 1.0 weight % to 6.0 weight % of iron element, 0.1 weight % to 6.0 weight % of nickel element, and 0.1 weight % to 1.5 weight % of manganese element, and a copper alloy stacking body with high density and excellent mechanical strength can be obtained.
[0139] That is, since the 50% particle size of the copper alloy powder particles measured by laser diffraction is within the range of 3 μm to 200 μm, the surface of the powder bed is not rough and has sufficient fluidity for easy application. In addition, since the apparent density of the copper alloy powder is 3.5 g / cm 3 As a result, the powder filling rate of the powder bed is sufficient, and an appropriate powder bed can be formed. In addition, since the adhesion of the copper alloy powder is 0.600 kPa or less, the powder can be smoothly supplied from the supply hopper, and an appropriate powder bed can be formed.
[0140] Furthermore, by adding 7.0% to 12.5% by weight of aluminum, 1.0% to 6.0% by weight of iron, 0.1% to 6.0% to 6.0% by weight of nickel, and 0.1% to 1.5% to 1.5% by weight of manganese, it is possible to produce a copper alloy stacked body having a relative density of 99.0% or more, a Vickers hardness of 150 Hv or more, an engineering stress of 500 MPa or more, a resistance of 180 MPa or more, and a wear amount of 0.01 g or less when the body is formed under conditions set based on energy density (which can be calculated from the output power of the laser, the scanning speed of the laser, the laser scanning interval, and the thickness of the powder bed).
[0141] Example
[0142] Hereinafter, Examples 1 to 5 and Comparative Examples 0 to 5 according to the first embodiment will be described.
[0143] <Manufacturing of Copper Alloy Powder for Laminated Molding>
[0144] Copper alloy powders to which aluminum is added are produced by gas atomization. Helium, argon, nitrogen, etc. are used as atomizing gas, and the pressure and flow rate of the gas are adjusted to produce copper alloy powders to which aluminum is added.
[0145] Copper alloy powder was produced by changing the content of aluminum element after addition to 0.6 wt% (Comparison Example 0), 1.3 wt% (Comparison Example 1), 2.0 wt% (Example 1), 5.0 wt% (Example 2), 7.0 wt% (Example 3), 10.0 wt% (Example 4), 12.0 wt% (Example 5), and 14.0 wt% (Comparison Example 2).
[0146] In addition, comparisons were made with copper fine powder produced by high-pressure water atomization (Comparative Example 3), copper spherical powder produced by a plasma rotating electrode method (Comparative Example 4), and copper powder produced by a gas atomization method (Comparative Example 5).
[0147] (Determination of properties of copper alloy powder for laminated molding)
[0148] The aluminum content in the copper alloy powder to which the aluminum element was added was measured by ICP emission spectrometry. In addition, the apparent density (g / cm 3 ). In addition, the fluidity (seconds / 50 g) of the copper alloy powder to which the aluminum element was added was measured in accordance with JIS Z 2502. In addition, the 50% particle size (μm) was measured by laser diffraction method (Microtrac MT3300: manufactured by MicrotracBEL Co., Ltd.). The properties of the copper alloy powders of Examples 1 to 5 and Comparative Examples 0, 1, and 2 manufactured are shown in Table 1. In addition, a shear test was carried out using a powder rheometer FT4 (manufactured by Freeman Technology Co., Ltd.), and the adhesion (kPa) of the obtained copper alloy powder was measured. In addition, it was determined whether the copper alloy powder can be coated using a fixture called a scraper or an applicator (a fixture that can process one side of a metal block to create a gap and apply paint, ink, etc. with a certain film thickness).
[0149] Table 1 shows the properties of the produced copper alloy powders of Examples 1 to 5 and Comparative Examples 0, 1, and 2, and the copper powders of Comparative Examples 3 to 5.
[0150] [Table 1]
[0151]
[0152] (Evaluation of properties of copper alloy powder for laminated molding)
[0153] According to Table 1, the copper alloy powder for lamination molding in Examples 1 to 5 and Comparative Examples 0, 1, and 2 meet the above-mentioned conditions for lamination molding using a lamination molding apparatus. That is, the powders (Examples 1 to 5 and Comparative Examples 0, 1, and 2) that meet (1) the 50% particle size of the powder particles (D50 in Table 1), (2) the apparent density of the powder (AD in Table 1), and (3) the adhesion (although the flowability (FR) of the powder cannot be measured (none.)) can be applied. On the other hand, the powders (Comparative Examples 3 to 5) that do not meet any of the conditions cannot be applied.
[0154] <Manufacturing of laminated shapes>
[0155] The copper alloy powders of Examples 1 to 5 and Comparative Examples 0, 1, and 2 that can be painted were used to produce laminated bodies using a 3D laminated molding machine (powder sintering laminated molding / SLM method: SLM280HL manufactured by SLM solutions). It should be noted that as a sample of the laminated body for characteristic measurement, a rectangular laminated body having a width of 10 mm, a depth of 7 mm, and a height of 5 mm was produced.
[0156] The copper alloy powders of Examples 1 to 5 and Comparative Examples 0, 1, and 2 were used to generate the powders using appropriate energy densities (J / mm 3 ) to produce a stacked structure. 3 ), as shown in Table 2. It should be noted that for the copper alloy powder for laminated molding to which 14.0 wt % of aluminum element was added, the energy density (J / mm 3 ) were varied to produce a stacked structure (see Comparative Examples 2-1 to 2-21).
[0157] [Table 2]
[0158]
[0159] As shown in Comparative Examples 2-1 to 2-21 in Table 2, the copper alloy powder for laminated molding to which 14.0 wt % of aluminum element was added all cracked even when the energy density was changed.
[0160] (Determination of properties of copper alloy laminated bodies)
[0161] The cross-sectional structure of the copper alloy laminated body produced was photographed using an optical microscope and the SEM (Scanning Electron Microscope) / EBSD (Electron BackScatter Diffraction) method, as well as the BC (Band Contrast) and KAM (Kernel Average Misorientation) diagrams. Figure 3 BC diagram 310 and KAM diagram 320 of a copper alloy laminated structure to which 7.0 wt % of aluminum element is added based on EBSD are shown, and an optical microscope photograph 330 of a copper alloy laminated structure to which 10.0 wt % of aluminum element is added is shown.
[0162] In addition, the properties of the manufactured copper alloy laminated body were measured using the test equipment shown in Table 3.
[0163] [Table 3]
[0164]
[0165] It should be noted that the test piece size 400 in the measurement of engineering stress, elongation, and endurance is shown in Figure 4 middle.
[0166] Table 4 shows the properties of the copper alloy laminated body measured using the test equipment shown in Table 3.
[0167] [Table 4]
[0168]
[0169] (Evaluation of properties of copper alloy laminated bodies)
[0170] Depend on Figure 3 From the BC graph 310 and the KAM graph 320, it can be seen that very fine columnar crystals with a width of about 1 μm or less grow in the forming direction, and high strain regions are distributed along these crystals. It is believed that the generation of such fine structures and strains is caused by the rapid cooling and solidification process in the stacking forming method. It is speculated that this is particularly helpful for the increase in endurance in the stacked forming body with 7.0 wt% aluminum added.
[0171] On the other hand, the laminated body with 10.0 wt% of aluminum added showed great work hardening, and the engineering stress also showed an extremely high value, but on the contrary, the endurance did not increase significantly. According to the organization observation based on the optical microscope photo 330 and the XRD analysis results, it can be confirmed that the copper alloy laminated body presents a plate-like β' martensite structure. It is believed that the reason why the endurance does not increase compared to the large work hardening or engineering stress is the martensitic transformation caused by the rapid solidification process during the laminated forming.
[0172] In addition, Figure 5 A graph showing the relationship between the aluminum content of the copper alloy powder for laminated molding and the engineering stress and the yield strength of the copper alloy laminated molding body is shown in FIG. 4 based on the characteristic measurement results obtained in Examples 1 to 5 and Comparative Examples 0 and 1. Figure 6 Graphs showing the relationship between the aluminum content of the copper alloy powder for laminated molding and the wear amount of the copper alloy laminated molding body based on the property measurement results of Table 4 obtained in Examples 1 to 5 and Comparative Examples 0 and 1 are shown in FIG.
[0173] From the measurement results of the properties of the copper alloy laminated body in Table 4 and Figure 5 and Figure 6As can be seen from the graph of , the mechanical strength of the copper alloy laminated body obtained by laminated molding using the copper alloy powder for laminated molding containing more than 1.3 wt% and less than 12.5 wt% of aluminum element becomes extremely high. That is, the copper alloy laminated body that satisfies Vickers hardness of more than 90.0 Hv, engineering stress (maximum stress) of more than 260 MPa, endurance of more than 160 MPa, and wear loss of less than 0.02 g can be obtained by laminated molding.
[0174] In addition, the upper limit of the aluminum element content of 12.5 weight% is calculated as follows. Figure 7 This is a diagram showing the quenching phase diagram of Cu-Al alloy and the calculation of the forming threshold. As shown in Table 4, stacking forming can be performed up to 12.0 wt% of aluminum, but when 14.0 wt% of aluminum is contained, cracks occur during stacking forming and stacking forming cannot be performed. Here, Figure 7 In the quenching phase diagram (710) of the Cu-Al alloy, the solid line represents the equilibrium phase diagram, and the dotted line phase diagram is formed when the cooling process is accompanied by quenching. The stacked forming is accompanied by quenching during the cooling process, so it becomes the constituent phase of the dotted line phase diagram. Figure 7 When the figure (720) showing the calculation of the forming threshold is shown, based on the quenching phase diagram (710), when the aluminum content is less than 12.5 weight %, the stacked body is composed of a β1' single phase. However, if the aluminum content is greater than 12.5 weight %, the γ' phase begins to precipitate, and when the aluminum content is 14.0 weight %, it becomes a γ' single phase. Therefore, it is believed that the precipitation of the γ' phase is the cause of cracks during stacking forming. It is speculated that if the aluminum content in which the γ' phase does not precipitate is within a range of 12.5 weight % or less, cracks will not occur and stacking forming can be performed.
[0175] In addition, if a proportional calculation is performed based on the results of 1.3 weight % of aluminum and the results of 2.0 weight % of aluminum, it is inferred that when the aluminum element is 1.7 weight % or more, a copper alloy stacked body that satisfies Vickers hardness of 90.0 Hv or more, engineering stress (maximum stress) of 260 MPa or more, endurance of 160 MPa or more, and wear amount of 0.02 g or less can be obtained by stacking.
[0176] In addition, according to the measurement results of the properties of the copper alloy laminated body in Table 4 and Figure 5 and Figure 6 As can be seen from the curve graph, the mechanical strength of the copper alloy laminated body obtained by laminated molding using the copper alloy powder for laminated molding containing 7.0 wt% or more and 12.5 wt% of aluminum element becomes higher. That is, the copper alloy laminated body that satisfies Vickers hardness of 150.0 Hv or more, engineering stress (maximum stress) of 500 MPa or more, endurance of 180 MPa or more, and wear loss of 0.01 g or less can be obtained by laminated molding.
[0177] Table 5 shows a threshold value group for evaluating the mechanical strength of the copper alloy laminated body set based on Examples 1 to 5. It should be noted that "≥ numerical value" means above the numerical value, and "numerical value ≥" means below the numerical value.
[0178] [Table 5]
[0179] Vickers hardness (Hv) Engineering stress (MPa) Endurance (MPa) Wear amount (g) Threshold Group 1 ≥90.0 ≥260 ≥160 0.02≥ Threshold Group 2 ≥150.0 ≥500 ≥180 0.01≥
[0180] <Tempering treatment of copper alloy laminated body>
[0181] The laminated body with 10.0 wt% of aluminum added showed great work hardening, and the engineering stress also showed an extremely high value, but on the contrary, the yield strength did not increase significantly. It is believed that the reason is the plate-like β' martensite structure and the martensite transformation caused by the rapid cooling solidification process during the laminated forming. Therefore, according to the second embodiment, after tempering at 400°C, 500°C, and 600°C for 1 hour, the characteristics related to mechanical strength were measured.
[0182] Table 6 shows the results of measuring the mechanical strength-related properties of the laminated shapes to which 10.0 wt % and 12.0 wt % of aluminum element were added after tempering.
[0183] [Table 6]
[0184]
[0185] In addition, Figure 8 Graphs showing the measurement results of the engineering stress and the proof stress with respect to the tempering temperature are shown in FIG.
[0186] (Evaluation of Tempering Treatment)
[0187] By tempering the copper alloy laminated body at a temperature slightly lower than the β-eutectoid decomposition temperature, the engineering stress decreases as the temperature rises, but is maintained at 500 MPa or more (about 600 MPa), and the yield strength increases. This result suggests that the structure of the copper alloy laminated body is fine.
[0188] exist Fig. 9 The equilibrium phase diagram of Cu-Al alloy is shown in Fig. 9 The equilibrium phase diagram shows a single-phase structure of α phase when the aluminum content is less than 9.0 wt%, but when the aluminum content is 9.4-15.6 wt%, a phase structure of (α+γ 2 ) is a eutectic phase. 2) region, the high temperature stable phase β is quenched, thereby showing a β' phase when the aluminum element is 10.0 wt%, and showing a β1' phase when the aluminum element is 12.0 wt%. It should be noted that the β' phase and the β1' phase become martensitic structures.
[0189] As described above, a large number of mobile dislocations are introduced during martensitic transformation, and therefore, movement begins at a low stress level, generating plastic strain corresponding to the number of dislocations that have moved. As a result, the yield strength is low, reflecting the movement of the mobile dislocations. By tempering the copper alloy laminated body containing 10.0% by weight of aluminum, the mobile dislocations in the copper alloy laminated body are reduced, and thus the yield strength is increased. It is inferred that the same effect is obtained even when the aluminum content is 12.0% by weight, showing the same martensitic structure.
[0190] Hereinafter, Examples 6 to 8 and Comparative Example 6 according to the third embodiment will be described.
[0191] <Manufacturing of Copper Alloy Powder for Laminated Molding>
[0192] Copper alloy powders to which aluminum, iron, nickel and manganese are added are produced by gas atomization. Helium, argon, nitrogen and the like are used as atomizing gases, and the pressure and flow rate of the gas are adjusted to produce copper alloy powders to which aluminum, iron, nickel and manganese are added.
[0193] Copper alloy powder was produced by making the following changes: the content of aluminum element after addition was 8.5 weight %, the content of iron element was 3.0 weight %, the content of nickel element was 0.5 weight %, and the content of manganese element was 0.1 weight % (Example 6); the content of aluminum element was 10.5 weight %, the content of iron element was 3.1 weight %, the content of nickel element was 2.0 weight %, and the content of manganese element was 1.1 weight % (Example 7); the content of aluminum element was 10.0 weight %, the content of iron element was 5.0 weight %, the content of nickel element was 5.0 weight %, and the content of manganese element was 0.7 weight % (Example 8); the content of aluminum element was 9.0 weight %, the content of iron element was 3.5 weight %, the content of nickel element was 2.5 weight %, and the content of manganese element was 11.0 weight % (Comparative Example 6).
[0194] (Determination of properties of copper alloy powder for laminated molding)
[0195] The contents of the various elements in the copper alloy powders of Examples 6 to 8 and Comparative Example 6 were measured by ICP emission spectrometry. In addition, the apparent densities (g / cm 3). In addition, the fluidity (seconds / 50 g) of the copper alloy powders of Examples 6 to 8 and Comparative Example 6 was measured in accordance with JIS Z 2502. In addition, the 50% particle size (μm) was measured using a laser diffraction method (Microtrac MT3300: manufactured by MicrotracBEL Co., Ltd.). The properties of the copper alloy powders of Examples 6 to 8 and Comparative Example 6 manufactured are shown in Table 7. In addition, a shear test was carried out using a powder rheometer FT4 (manufactured by Freeman Technology Co., Ltd.), and the adhesion (kPa) of the obtained copper alloy powder was measured. In addition, it was determined whether the copper alloy powder can be coated using a fixture called a scraper or an applicator (a fixture that can process one side of a metal block to create a gap and apply a coating, ink, etc. with a certain film thickness).
[0196] Table 7 shows the properties of the copper alloy powders of Examples 6 to 8 and Comparative Example 6 produced.
[0197] [Table 7]
[0198]
[0199] (Evaluation of properties of copper alloy powder for laminated molding)
[0200] According to Table 7, the copper alloy powder for lamination molding in Examples 6 to 8 and Comparative Example 6 meets the above-mentioned conditions for lamination molding using a lamination molding apparatus. That is, the powders (Examples 6 to 8 and Comparative Example 6) satisfy (1) the 50% particle size of the powder particles (D50 in Table 7), (2) the apparent density of the powder (AD in Table 7), and (3) the adhesion (although the flowability (FR) of the powder cannot be measured (none.)), and can be applied by brushing.
[0201] It should be noted that regarding the content of each element in the copper alloy powders of Examples 6 to 8 and Comparative Example 6, the appropriate weight % of each element was verified by setting the weight % with attention paid to the content of each element in the conventional copper alloy castings shown in Table 8.
[0202] [Table 8]
[0203]
[0204] <Manufacturing of laminated shapes>
[0205] The copper alloy powders of Examples 6 to 8 and Comparative Example 6 that can be painted were used to produce laminated bodies using a 3D laminated molding machine (powder sintering laminated molding / SLM method: SLM280HL manufactured by SLM solutions). It should be noted that as a sample of the laminated body for characteristic measurement, a rectangular laminated body having a width of 10 mm, a depth of 7 mm, and a height of 5 mm was produced.
[0206] The copper alloy powders of Examples 6 to 8 and Comparative Example 6 were used to obtain the powders with appropriate energy density (J / mm 3 ) to produce a stacked structure. 3 ), as shown in Table 9. It should be noted that the energy density (J / mm 3 ) were varied to produce a stacked structure (see Comparative Examples 6-1 to 6-30).
[0207] [Table 9]
[0208]
[0209] As shown in Comparative Examples 6-1 to 6-30 in Table 9, the copper alloy powders for stacking molding obtained by adding an aluminum content of 9.0 wt%, an iron content of 3.5 wt%, a nickel content of 2.5 wt%, and a manganese content of 11.0 wt% all produced cracks even when the energy density was changed.
[0210] Table 10 shows the properties of the copper alloy laminated bodies obtained by molding using the copper alloy powders in Examples 6 to 8 and Comparative Example 6, measured using the test equipment shown in Table 3.
[0211] [Table 10]
[0212]
[0213] exist Figure 5 In the present invention, the relationship between the aluminum content of the copper alloy powder for laminated molding and the engineering stress and the yield strength of the copper alloy laminated molding body is added based on the characteristic measurement results of Table 10 obtained in Examples 6 to 8. Figure 6 In the above, based on the characteristic measurement results of Table 10 obtained in Examples 6 to 8, the relationship between the aluminum content of the copper alloy powder for laminated molding and the wear amount of the copper alloy laminated body is added.
[0214] From the measurement results of the properties of the copper alloy laminated body in Table 10 and Figure 5 and Figure 6 As can be seen from the curve graph, the mechanical strength of the copper alloy laminated body obtained by laminating and molding using the copper alloy powder for laminating and molding containing 7.0 wt% to 12.5 wt% of aluminum, 1.0 wt% to 6.0 wt% of iron, 0.1 wt% to 6.0 wt% of nickel, and 0.1 wt% to 1.5 wt% of manganese becomes extremely high. That is, the copper alloy laminated body that satisfies Vickers hardness of 150.0 Hv or more, engineering stress (maximum stress) of 500 MPa or more, endurance of 180 MPa or more, and wear loss of 0.01 g or less can be obtained by laminating and molding.
[0215] In addition, by adding iron, nickel, and manganese, it is expected that corrosion resistance will be improved. In Example 6, even though the aluminum content is low, the engineering stress (maximum stress) and the endurance are increased, and the elongation is also obtained. For example, even compared with Example 4 in which the aluminum content is 10% by weight, Examples 7 and 8 with the same aluminum content can improve the elongation without reducing the strength.
[0216] From the above, it was confirmed that according to Examples 1 to 8, a copper alloy powder for laminated molding that can achieve excellent mechanical strength and a copper alloy laminated molding having excellent mechanical strength can be provided. In addition, it is believed that when tempering is performed, advantages such as improved strength and other improved properties can be observed, which has superiority as a manufacturing method.
[0217] (Field of application of the present invention)
[0218] The copper alloy laminated body according to the present invention can be suitably used for parts such as bearings, pistons, ship propellers, pumps, etc. that require particularly high mechanical strength (Vickers hardness, engineering stress, endurance, wear, etc.).
[0219] This application claims the benefit of priority based on Japanese patent application No. 2022-077233, filed on May 9, 2022, the disclosure of which is hereby incorporated by reference in its entirety.
Claims
1. A copper alloy powder for laminated molding, the copper alloy powder being used for molding a laminated body by a laminated molding method, The copper alloy powder for laminated molding contains more than 1.3 wt % and less than 12.5 wt % of aluminum element, and the remainder is composed of copper and inevitable impurities.
2. The copper alloy powder for laminated molding according to claim 1, comprising 7.0 wt% to 12.5 wt% of the aluminum element, with the remainder being copper and unavoidable impurities.
3. The copper alloy powder for laminated molding according to claim 1 or 2, wherein: The 50% particle size of the copper alloy powder for laminated molding is 3 μm or more and 200 μm or less.
4. The copper alloy powder for laminated molding according to claim 1 or 2, wherein: The apparent density of the copper alloy powder for laminated molding measured by the measuring method of JIS Z 2504 was 3.5 g / cm 3 above. 5 . The copper alloy powder for laminated molding according to claim 1 , wherein the adhesion of the copper alloy powder for laminated molding is 0.600 kPa or less, wherein the adhesion is obtained from a failure envelope obtained by a shear test using a powder rheometer.
6. A method for producing a copper alloy powder for laminated molding, which is the method for producing a copper alloy powder for laminated molding according to claim 1, comprising the following steps: A step of generating a copper alloy powder by gas atomization, wherein the copper alloy powder is obtained by adding more than 1.3 wt % and less than 12.5 wt % of aluminum to copper; and A step of classifying the produced copper alloy powder into a particle size of 10 μm or more and 45 μm or less.
7. A copper alloy laminated body obtained by laminating and molding the copper alloy powder for laminating molding according to claim 1 using a laminating and molding apparatus, The copper alloy laminated body contains more than 1.3 wt % and less than 12.5 wt % of aluminum, and the remainder is composed of copper and inevitable impurities.
8. The copper alloy laminated body according to claim 7, wherein: The copper alloy laminated body has a relative density of more than 99.0%, a Vickers hardness of more than 90 Hv, an engineering stress of more than 260 MPa, a resistance of more than 160 MPa, and a wear loss of less than 0.02 g.
9. A copper alloy laminated body obtained by performing laminated molding using the copper alloy powder for laminated molding according to claim 2 and a laminated molding apparatus. The copper alloy laminated body contains 7.0 wt % or more and 12.5 wt % or less of aluminum, and the remainder is composed of copper and inevitable impurities. The copper alloy laminated body has a relative density of more than 99.0%, a Vickers hardness of more than 150 Hv, an engineering stress of more than 500 MPa, a bearing strength of more than 180 MPa, and a wear loss of less than 0.01 g.
10. A method for producing a copper alloy laminated body, comprising the following steps: A manufacturing process, using the copper alloy powder for laminated molding according to claim 1 or 2, and manufacturing a copper alloy laminated body using a laminated molding device; and In the tempering step, the copper alloy laminated body is kept at a temperature of 400° C. to 600° C. for 1 hour.
11. A copper alloy powder for laminated molding, the copper alloy powder for laminated molding being used for molding a laminated body by a laminated molding method. The copper alloy powder for stacked molding contains more than 7.0 weight % and less than 12.5 weight % of aluminum, more than 1.0 weight % and less than 6.0 weight % of iron, more than 0.1 weight % and less than 6.0 weight % of nickel, and more than 0.1 weight % and less than 1.5 weight % of manganese, with the remainder being copper and unavoidable impurities.
12. A method for producing copper alloy powder for laminated molding, which is the method for producing copper alloy powder for laminated molding according to claim 11, comprising the following steps: A step of generating a copper alloy powder by gas atomization, wherein the copper alloy powder is obtained by adding greater than 7.0 wt% and less than 12.5 wt% of aluminum, greater than 1.0 wt% and less than 6.0 wt% of iron, greater than 0.1 wt% and less than 6.0 wt% of nickel, and greater than 0.1 wt% and less than 1.5 wt% of manganese to copper; and A step of classifying the produced copper alloy powder into a particle size of 10 μm or more and 45 μm or less.
13. A copper alloy laminated body obtained by performing laminated molding using the copper alloy powder for laminated molding according to claim 11 and using a laminated molding apparatus, The copper alloy stacked shape contains more than 7.0 weight % and less than 12.5 weight % of aluminum, more than 1.0 weight % and less than 6.0 weight % of iron, more than 0.1 weight % and less than 6.0 weight % of nickel, and more than 0.1 weight % and less than 1.5 weight % of manganese, with the remainder being copper and unavoidable impurities.
14. The copper alloy laminated body according to claim 13, wherein the relative density is 99.0% or more, the Vickers hardness is 150 Hv or more, the engineering stress is 500 MPa or more, the endurance is 180 MPa or more, and the wear loss is 0.01 g or less.
